LPM Suara Kampus IAIN Imam Bonjol Padang - Habil Ramanda; Hendra Naldi (PAMA Aksara, 2023)
This research discusses LPM Suara Kampus State Islamic Institute (IAIN) Imam Bonjol Padang Period NKK/BKK to SK No.4003/U/1990 New Order Period. The Normalization of Campus Life which was implemented during the era of the Minister of Education and Culture Daoed Joesoef was the government's attempt to keep students away from the social and political affairs of the government. Under the supervision of the Student Affairs Coordinating Board (BKK), all tertiary student organizations throughout Indonesia are regulated and supervised in carrying out their activities, including student publications on campus. At IAIN Imam Bonjol Padang, a campus press was published named Shautul Al-Jamiah/ Suara Kampus 1979. The focus of this research study is to discuss the existence of news Suara Kampus in the period of the NKK/BKK policy and its existence after the policy was repealed in 1990. The purpose of this study is to reveal the existence of LPM reporting Suara Kampus in the period of the NKK BKK policy to SK No.4003/U/1990 during the New Order. This research includes qualitative research, using historical research methods. Qualitative research is a research procedure that produces descriptive data. The steps in historical research go through four stages, namely heuristics (searching for and collecting data), source criticism, interpretation (interpreting historical facts or evidence) and historiography (history writing). The data collection techniques used were archival studies, literature studies and interviews. The research results show that Suara Kampus when the NKK/BKK policy was implemented, it was still able to show its existence by consistently publishing tabloids, newspapers and magazines that contained news reviews about campuses and articles on Islamic themes. The publication received international recognition by being invited Suara Kampus to the World Islamic Media Conference. After the NKK/BKK policy was repealed, Suara Kampus still exists by incorporating socio-political issues so that the rubrics presented are more diverse.